A minhei mongvorok temetési szokásai - Simonkay, Zsuzsanna (Távol-keleti Tanulmányok, 2017)
The Minhe Monguors are a Mongolic ethnicity numbering around 30,000 people, who live in Qinghai 青海 and Gansu 甘肃 provinces in China. Although a few Western and Chinese scholars have already conducted research among this group from the early 20th century up to the present day, they are still little known in the international scholarly world, and even less known in Hungary. In this paper, based on the studies of Louis M. J. Schram (mid-20 th century) and Kevin Stuart (late 20 th century), with additional observations I made during my field research in 2007, I discuss Minhe Monguors’ burial practices. I also make some remarks on the similarities and differences between the practices of the Minhe Monguors and the Mongols of Mongolia, and interpret the customs that are not of Mongolian origin.